El juego didáctico para fortalecer el desarrollo cognitivo de los niños y niñas de 4 a 5 años del centro de educación inicial “Pío Jaramillo Alvarado” de la ciudad de Loja. Periodo lectivo 2013-2014 - Vera Rey, Liliana Elizabeth (2016)
The title of the current researching is: THE DIDACTIC GAME TO STRENGTHEN THE COGNITIVE DEVELOPMENT OF CHILDREN FROM 4 TO 5 YEARS OF THE EARLY EDUCATION CENTER “PIO JARAMILLO ALVARADO” OF LOJA CITY. SCHOOL PERIOD 2013-2014, the general objective is to establish the relation between the cognitive development and the frequency of application of the didactic game in the formation process of children from 4 to 5 years old, the used methods were: comprehensive, analytical, synthetic, participatory diagnosis, models or proactive. The instrument used was the cognitive skills test to determine the cognitive development of children from 4 to 5 years of early education and the technical survey addressed to teachers to diagnose the frequency of the application of the didactic games in the daily work.The most relevant works mentioned through the applied instruments to the total population of 138, break down into seven teachers and 131 children. It is evident by the test of cognitive skills that the 74% of studied children have a cognitive development very satisfying, while the 26% of children register unsatisfying, therefore, it is concluded that the game has a direct relation with the cognitive development, favoring the language, thought, perception, memory, attention, concentration, troubleshooting and experience in the world.The survey applied to teachers expressed to perform the didactic game with children the 86%, while the 14% is performed sometimes, emphasizing that all of them, namely the 100%, execute games of temporal dimension, songs and finger plays, finally 71% perform verbal games. With this regard, it was considered to propose a methodology guide of didactic games of easy application with children from 4 to 5 years to improve the levels of cognitive development of the children that obtained unsatisfactory. Finally, it is recommended to teachers: to employ several strategies that involve the didactic game, and apply them whenever is necessary in the daily work. Furthermore, to optimize the pedagogic training with methodological strategies interactive and recreational, according to the characteristics of the children, since the game constitutes the primary occupation of the child, and obtaining a progressive level of development and learning